2019
DOI: 10.3390/ijerph16244979
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Evaluating a Digital Family Health History Tool for Spanish Speakers

Abstract: Digital family health history tools have been developed but few have been tested with non-English speakers and evaluated for acceptability and usability. This study describes the cultural and linguistic adaptation and evaluation of a family health history tool (VICKY: VIrtual Counselor for Knowing Your Family History) for Spanish speakers. In-depth interviews were conducted with 56 Spanish-speaking participants; a subset of 30 also participated in a qualitative component to evaluate the acceptability and usabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…We aimed to recruit participants who were 18 years or older but made no further specifications for age, gender, race, or education. However, our findings were consistent with previous studies with well-educated and underserved populations ( 11 14 ).…”
Section: Discussionsupporting
confidence: 93%
“…We aimed to recruit participants who were 18 years or older but made no further specifications for age, gender, race, or education. However, our findings were consistent with previous studies with well-educated and underserved populations ( 11 14 ).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have identified intergenerational tension or hesitation to share health information, which is perceived to be private, as a barrier to FCH communication among older and younger relatives (7,12). Recently, Hood drew attention to the importance of incorporating cultural context and addressing racial/ethnic disparities in family health history research and development of culturally appropriate interventions to increase family communication about health (20). One promising example, a Spanish-language digital family health history tool, demonstrated acceptability and usability among Spanish-speaking families for collecting health information among a culturally and linguistically diverse population (21).…”
Section: Discussionmentioning
confidence: 99%
“… 57 Limited prior research has examined availability of FHI across patient subgroups. 59 , 60 , 61 , 62 However, previous research has shown multiple barriers to the collection of FHI generally, including limited time, competing demands, reimbursement criteria, and clinician and staff training and knowledge. 63 , 64 , 65 , 66 , 67 Prior studies have also shown underuse of FHI owing to incomplete or inaccurate information, lack of awareness about hereditary cancers, lack of awareness of evidence-based guidelines, and time constraints.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancer FHI may help determine what type of genetic testing is ordered . Limited prior research has examined availability of FHI across patient subgroups . However, previous research has shown multiple barriers to the collection of FHI generally, including limited time, competing demands, reimbursement criteria, and clinician and staff training and knowledge .…”
Section: Discussionmentioning
confidence: 99%